Influence of indium concentration and growth temperature on the structural and optoelectronic properties of indium selenide thin films. Issue 1 (19th September 2012) - Sreekumar, R.; Sajeesh, T. H.; Abe, T.; Kashiwaba, Y.; Sudha Kartha, C.; Vijayakumar, K. P.
Abstract The present work reports the influence of indium concentration and annealing temperature (100–400 °C) on the structural and optoelectronic properties of indium selenide thin films grown using a stack elemental layer technique. The concentration of indium in indium selenide thin films is varied by adjusting the thickness of the indium layer to 28, 42 or 56 nm while keeping the selenium layer thickness constant at 200 nm. Depending on the indium layer thickness of 42 or 56 nm, indium selenide thin films exhibited a phase transition either from a mixed phase (InSe, γ‐In2Se3 and β‐In2Se3) and/or from a complete amorphous phase to a single phase γ‐In2Se3 at annealing temperature 400 or 300 °C, respectively, with a preferential grain orientation along the c‐axis. Depth‐wise X‐ray photoelectron spectroscopy (XPS) analysis conducted on these samples (thickness of Se = 200 nm, In = 56 nm) showed evidence of a phase transition from amorphous to crystalline γ‐In2Se3 phase and formation of uniform stoichiometric (In/Se = 40:60) indium selenide. On the other hand, indium selenide grown using an indium thickness of 28 nm did not exhibit any phase transition. While using X‐ray diffraction (XRD) studies to analyse the structural properties, we made use of optical absorption and Raman spectroscopy in order to determine the optical energy gap and find the presence of parasitic β‐In2Se3 phase, respectively. The growth along the c‐axis either gives rise to carrier diffusion along the c‐axis or causes the appearance of a higher photosensitivity (62–72) due to the absence of dangling bonds which trap photogenerated carriers. The properties exhibited by the c‐axis‐grown γ‐In2Se3 suggest the potentiality of this material as a window layer in solar cell application.